Akuntansi berkomputer. Dari konsep strategis. Siklus akuntansi hingga penerapan - PURNOMOSIDI, Bambang (BPFE YOGYA, 1999)
Akuntansi berkomputer. Dari konsep strategis. Siklus akuntansi hingga penerapan